1994
DOI: 10.1002/pd.1970141014
|View full text |Cite
|
Sign up to set email alerts
|

Hyperechoic fetal bowel: The perinatal consequences

Abstract: A number of publications have reported an association between the finding of hyperechoic fetal bowel on prenatal sonogram and disorders such as aneuploidy and cystic fibrosis. To define more precisely the significance of this finding, we systematically reviewed the published material on the subject. Based on a total of 357 reported cases, we documented a high prevalence of cystic fibrosis (25.6 per cent) and chromosome abnormality (12.4 per cent) associated with increased bowel echogenicity in the fetus. High … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 16 publications
0
22
1
Order By: Relevance
“…Sepulveda et al [17] did not find an association between FEB and an increased incidence of CF mutations in 45 pregnancies at low risk for this disease. In contrast, in a review of 357 published cases, Bahdo-Singh et al [5] found CF mutations in 25.6% of cases with FEB. In a recent article, Slotnick and Abuhamad [7] stated that they offer their patients genetic couseling, parental CF-carrier testing, and amniocentesis for fetal karyotype only when the echogenicity of the fetal bowel is equal to or greater than that of the iliac crest.…”
Section: Discussionmentioning
confidence: 93%
“…Sepulveda et al [17] did not find an association between FEB and an increased incidence of CF mutations in 45 pregnancies at low risk for this disease. In contrast, in a review of 357 published cases, Bahdo-Singh et al [5] found CF mutations in 25.6% of cases with FEB. In a recent article, Slotnick and Abuhamad [7] stated that they offer their patients genetic couseling, parental CF-carrier testing, and amniocentesis for fetal karyotype only when the echogenicity of the fetal bowel is equal to or greater than that of the iliac crest.…”
Section: Discussionmentioning
confidence: 93%
“…8). [74][75][76][77][78] Hyperechoic bowel has also been reported in association with bowel atresia, congenital infection, and, rarely, meconium ileus secondary to cystic fibrosis. 79,80 An increased risk of IUGR, fetal death, and placenta-related complications is also recognized as being associated with hyperechoic bowel.…”
Section: Hyperechoic Bowelmentioning
confidence: 99%
“…2,5,7,8 Muller and coworkers, however, described a prospective study of 87 patients with hyperechoic bowel in a low-risk population and found a 4% risk of chromosomal anomalies and 5% risk of cystic fibrosis. 15 Similarly, Vintzileos and Egan 13 reported a poor sensitivity of 7%.…”
Section: Discussionmentioning
confidence: 99%